2017
DOI: 10.1111/asj.12888
|View full text |Cite
|
Sign up to set email alerts
|

Determination of net energy content of soybean oil fed to growing pigs using indirect calorimetry

Abstract: The objectives of this experiment were: (i) to determine the net energy (NE) of soybean oil (SBO) fed to growing pigs using indirect calorimetry (IC); and (ii) to evaluate the effects of inclusion rate of SBO on heat production, oxidative status and nutrient digestibility in growing pigs. Eighteen growing barrows were allotted to three diets based on completely randomized design with six replicate pigs (period) per diet. Diets included a corn-soybean meal basal diet and two test diets containing 5% or 10% SBO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
9
9
0
Order By: Relevance
“…Some studies reported that increasing DF level by graded inclusion of WB or sugar beet pulp decreased digestion of energy and other nutrients (Huang et al, ; Zhang et al, ). The impact of dietary fat level on ATTD of EE in the current study was in agreement with Li et al () where ATTD of crude fat linearly increased when dietary fat level increased. It can be explained that the endogenous concentration of fat had a greater effect on the apparent fat digestibility at low dietary fat levels than at higher levels (Kil, Sauber, Jones, & Stein, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies reported that increasing DF level by graded inclusion of WB or sugar beet pulp decreased digestion of energy and other nutrients (Huang et al, ; Zhang et al, ). The impact of dietary fat level on ATTD of EE in the current study was in agreement with Li et al () where ATTD of crude fat linearly increased when dietary fat level increased. It can be explained that the endogenous concentration of fat had a greater effect on the apparent fat digestibility at low dietary fat levels than at higher levels (Kil, Sauber, Jones, & Stein, ).…”
Section: Discussionsupporting
confidence: 93%
“…The impact of dietary fat level on ATTD of EE in the current study was in agreement with Li et al (2017) where ATTD of crude fat linearly increased when dietary fat level increased. It can be explained that the endogenous concentration of fat had a greater effect on the apparent fat digestibility at low dietary fat levels than at higher levels (Kil, Sauber, Jones, & Stein, 2010).…”
Section: Effect Of Fibre Type and Level On Nutrient Digestibility Asupporting
confidence: 89%
“…Dietary fiber has a negative effect on EE digestibility (Noblet & Le Goff, ), but pigs fed the PKE diets had the greater ATTD of EE. Previous studies also reported that the ATTD of EE increased as dietary fat intake increased (Jørgensen, Jakobsen, & Eggum, ; Li, Lv, et al., ), indicating that the endogenous fat has a greater influence on the apparent fat digestibility at low dietary levels than at higher levels (Li, Lv, et al., ). Data for the ATTD of CP confirm that pigs fed OB, WB, and PKE diets had greater nitrogen output from feces.…”
Section: Discussionmentioning
confidence: 85%
“…According to previous studies, litter performance and feed intake are affected by increasing energy density in a hot environment (Choi et al, ; Renaudeau & Noblet, ). Based on the net energy system for sows, the relative heat increment of supplementary fat during the digestion process is lower than starch (Li et al, ). Therefore, a lower heat increment can be expected in sows fed high‐fat diets.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the net energy system for sows, the relative heat increment of supplementary fat during the digestion process is lower than starch (Li et al, 2018). Therefore, a lower heat increment can be expected in sows fed high-fat diets.…”
Section: Discussionmentioning
confidence: 99%